The role of the INTERPOL in the counter-terrorism in Iraq 2003-2017 - Al-Rikabi, Mustafa Kadhim (Penerbit Universiti Kebangsaan Malaysia, 2021)
Terrorism poses threat to International peace and security. To avert the threat posed by transnational terrorists, members of the International Criminal Police Organization (INTERPOL), including Iraq, have been working together to counter transnational terrorist attacks. The article identifies the level of performance of INTERPOL counter terrorism in Iraq, to determine the factors that affect the improvement of the performance of INTERPOL counter-terrorism and to identify the barriers faced by Interpol in its counter-terrorism efforts. This article uses qualitative methods to investigate the development of international counter-terrorism of INTERPOL. This in turn enables a more in-depth insight regarding the current role of the INTERPOL in countering terrorism. The cooperation among INTERPOL member countries depends on various factors such as training of staff, political stability of the members, technology used in combating terrorism and conducting counter-terrorism and the conduct of investigation and interrogation. All these factors have an impact on the effectiveness of the implementation of counter-terrorism efforts at the national level and the cooperation between INTERPOL Member Countries. In particular the study refers to the development in Iraq that has some impact on the effectiveness of Iraqi INTERPOL to conduct counter-terrorism activities. This article asserted four main factors determining the function of Interpol in countering terrorism: Staff Training, Political instability, Technology Support and Interrogation.